Reason, Authority and the Text - Louay M. Safi (International Institute of Islamic Thought, 2000)
Modem thought rose out of a fierce and protracted struggle in Europe between the pre-modem religious tradition, which located ultimate truth in divine text, and a philosophical tradition which placed truth in human experience and insisted that truth could be attained through the intellectual examination of human reality. Enlightenment scholars succeeded indeed not only in defending the autonomy of rationality and reason, but also in using human intellect to develop modem social sciences. Methodical and systematic approaches to understanding human experience propelled modem scholarship forward in its attempts to provide a better understanding of human psyche and condition. This led to the development of elaborate theories and research methods in the areas of social studies, economics, politics, psychology, administration, and others. While modem scholarship made impressive advances by using analytical reasoning to shed light on social phenomena, it hit a solid wall in its efforts to base value systems on an empirically defined rationality. Many modem scholars were initially inclined to shrug off the importance of values to social knowledge and social understanding. Some even tried to deny the transcendental nature of values. Ultimately though, the dominant positivist school was forced to give up its attempt to build human knowledge on a purely empirical basis. The failure of modem thought to develop a purely rational scholarly tradition has emboldened postmodem writers, and encouraged them to deny the possibility of pursuing truth. Hence rationalism has been placed on an equal footing with irrationality, and morality has been equated with immorality. Power of Reason The intellectual impasse we all face today may be traced back to the Enlightenment scholars' efforts to sever human values from their transcendental base, and to marginalize the irqportance of religious beliefs, or the lack thereof, in shaping the scholar's attitude, and in providing the transcendental presuppositions essential for social research. However, modem ...